The Weight of Gold : Mining and the Environment in Ontario, Canada, 1909-1929 - Jorgenson, Mica, 1987- (Book collections on Project MUSE., 2022)
"The Weight of Gold tells the story of the rise of Canadian gold mining and its environmental consequences in the Abitibi region of northern Ontario in the early twentieth century. It connects Canadian gold mining to its international context and demonstrates how mining companies redistribute the harms associated with extraction to nearby communities"--